Floral visitors and their behavior to sympatric Salvia species (Lamiaceae) in Mexico - Dieringer, Gregg; Ramamoorthy, T.P.; Tenorio Lezama, Pedro (Instituto de Ecología, A.C., 1991)
A field survey in southwestern México was undertaken to lócate and identify sympatrically flowering populations of Salvia and to characterize their visiting bee faunas. Twenty nine species of Salvia were observed and 33 species of bees collected. The most common bee visitors were Bombus species comprising 66% of the bee species collected. Of the 36 localities visited, 42% had sympatric, concurrently flowering Salvia species. As many as five flowering Salvia species may co-occur and share pollinating visits from the same bee species. Potential interactions between Salvia species and their pollinating beesare discussed.